Crimes against Animals - Darwish, Colgin Ali Akbar; Mohammed, Abbas Qasim (Journal of Ecohumanism, 2024)
This study delves into the proportionality of the Iraqi legislator’s treatment of crimes against animals, the potential legislative flaws in the Iraqi Penal Code, and the issue of enforcement of these provisions require a more in-depth analysis of the legal texts and their practical application. The present research employs a methodological approach to examine the crimes of killing animals and causing them harm, as addressed in the Iraqi Penal Code No. 111 of 1969. This involves analyzing the relevant legal provisions and evaluating the adequacy and proportionality of the legislator’s treatment of such crimes.Findings showed that, in the Iraqi law, the animal is considered the victim of the crime, and it enjoys criminal protection to limit the crimes committed against it. Islamic law prohibits the killing or harming of an animal without justification, and considers that an assault on the animal’s ownership. The Iraqi law imposes penalties on crimes committed against animals, whether intentional or negligent, and the penalties vary between imprisonment and fines. The study recommends the Iraqi legislator to amend the Penal Code to remove the requirement of animal ownership, expand the protection to unowned animals, and strengthen the punishments for intentional killing or harm to animals, in order to better safeguard animal wealth. Additionally, raising public awareness about the importance of animals for environmental balance through ethical education and awareness programs is crucial.